The place of women in police education the situation and perspective of women's human rights - Spasić Danijela (Temida)
In this paper, the author attempts to establish, based on specific characteristics and on the openness of police education in Serbia and other Western Balkan countries, the extent to which equal rights of women and men concerning the accessibility to police education are respected, as well as their rights concerning the possibility of finding a job, building a career and their professional orientation in the police. All of that in light of respecting women' s human rights granted by the most important international documents on human rights, especially by the Convention on the Elimination of all Forms of Discrimination against Women (CEDAW). Analyzing the situation of women in police education and within the police of different countries, first of all in those of Europe and the Western Balkans, and especially in Serbia, the author will establish the degree of conformity, but also the gap between de jure and de facto situations.